Circulating and urinary microRNAs as possible biomarkers in kidney transplantation - Janszky, Noémi; Süsal, Caner (Transplantation reviews, 2018)
The invasive needle biopsy is currently the only established technique to distinguish between different types of kidney allograft damage and there is an urgent need for the development of reliable non-invasive methods for the timely recognition of upcoming rejection episodes. microRNAs (miRNAs) belong to a class of small non-coding RNAs that modulate physiological and pathological processes by regulating gene expression via post-transcriptional inhibition of target messenger RNAs (mRNAs). Recently, miRNAs were detected in remarkably stable forms in human body fluids and found to be involved in pathological processes that occur following kidney transplantation. In this review we discuss the critical issues around the detection and quantification of miRNA expression and summarize the recently published preliminary findings on miRNAs as possible biomarkers for the diagnosis of allograft rejection after kidney transplantation.